PERJANJIAN PERKAWINAN YANG DIBUAT SETELAH PERKAWINAN DAN AKIBAT HUKUMNYA DITINJAU DARI KITAB UNDANG-UNDANG HUKUM PERDATA - FITRIYANI FITRIYANI (PREMISE LAW JURNAL, 2014)
ABSTRACT Marriage agreement after the marriage is an agreement between husband and wife to regulate the consequence inflicted by the marriage law against their property which is made after their marriage through the Decision of State Court. Marriage agreement after the marriage issued under the decision of State Court is made based on the agreement of the parties involved and the authority of justice stating that the Court is not allowed to reject any incoming application. The purpose of the making of marriage agreement after the marriage is to regulate the legal consequences against the property, debt and accounts receivable and the agreement on the other important issues after the date of issuance of a legal marriage agreement. Legal consequence resulted from the marriage agreement made after the marriage inflicts legal consequence to the those who made it, the property obtained during marriage, and to the related third party. Keywords: Marriage Agreement, After Marriage, Legal Consequence